Narcissistic Tendencies, Psychological Need Satisfaction, And Selfie-Taking Behavior in Youth - Nawaz, Safa; Asghar, Fatima; Ayub, Sumaira (Journal of Pakistan Psychiatric Society, 2025)
Objective: To explore the relationship between narcissistic tendencies, psychological need satisfaction and selfie-taking behaviour in youth.Study Design: Research design of the study was correlational cross-sectional.Place and Duration of Study: The study was conducted between March 2023 to February 2024 in the Department of Applied Psychology, University of Management and Technology Lahore.Subjects and Methods: The sample comprised of 200 youth with age range of 18 to 30 years (M= 21.99, SD=2.25) including 79 men and 121 women. The data was collected from eight different universities of Lahore by employing convenience sampling technique. A self-constructed demographic information sheet, Narcissistic tendencies Inventory Scale (NPI-16), Basic Need Satisfaction in General Scale and Selfitis Behaviour Scale were used for the assessments.Results: The result indicated the positive relationship between narcissistic tendencies and selfie-taking behavior and negative relationship was found between psychological need satisfaction and selfie-taking behavior. Furthermore, no relationship was found between narcissistic tendencies and psychological need satisfaction. The result showed that narcissistic tendencies positively predicted the selfie-taking behavior, however psychological need satisfaction did not predict it. The results also showed men scored higher on narcissism and selfie-taking behavior.Conclusion: The present study helped us know how selfie-taking behaviors are related to narcissistic tendencies in young educated sample.